1988
DOI: 10.1017/s0021859600083696
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combinations of organic materials and nitrogen fertilizer on growth, yield and nitrogen uptake of rice

Abstract: SummaryIn a 2-year study, the growth and yield of lowland rice increased significantly with the combined use of organic materials and N fertilizer in an acid-lateritic soil. Application of farmyard manure (FYM) or water hyacinth compost (WHC) at 10 t/ha along with paddy straw (PS) at 2·5 t/ha increased grain yield by 28%, similar to the increase given by 30 kg N/ha as fertilizer. The combination of FYM and WHC with or without PS produced yields equivalent to those using 50–60 kg/ha N as fertilizer urea. Uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 4 publications
3
18
0
1
Order By: Relevance
“…Similar long-term studies on different crops have shown increased yield due to application of FYM, and these effects were attributed largely to improved soil organic matter, and soil physical, chemical, and microbial properties (Belay et al, 2001;Satyanarayana et al, 2002). Application of FYM also influences plant growth physiologically by providing growth-regulating substances (Flaig, 1974 as cited by Sharma and Mittra, 1988).…”
Section: Downloaded By [Mcmaster University] At 07:37 26 November 2014mentioning
confidence: 94%
See 1 more Smart Citation
“…Similar long-term studies on different crops have shown increased yield due to application of FYM, and these effects were attributed largely to improved soil organic matter, and soil physical, chemical, and microbial properties (Belay et al, 2001;Satyanarayana et al, 2002). Application of FYM also influences plant growth physiologically by providing growth-regulating substances (Flaig, 1974 as cited by Sharma and Mittra, 1988).…”
Section: Downloaded By [Mcmaster University] At 07:37 26 November 2014mentioning
confidence: 94%
“…It is commonly believed that the combination of organic and inorganic fertilizer will increase synchrony and reduce losses by converting inorganic nitrogen (N) into organic forms (Kramer et al, 2002) and is important not only for enhancing the efficiency of the fertilizers, but also in reducing environmental problems that may arise from their use. Apart from supplying nutrients, the application of organic substances, including farmyard manure, also provides growth-regulating substances (Flaig, 1974 as cited by Sharma and Mittra, 1988) and improves the physical (El-Shakweer et al, 1998), chemical (Schjonning et al, 1994), and microbial (Belay et al, 2001) properties of the soil.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient contribution of recycled RS depends mainly on the quantity applied, the composition of RS and its management. Long-term experiments indicate that RS incorporation in wetland rice fields increased available N, P, K and Si contents of the soil and therefore helped to increase paddy yields (Ponnamperuma 1984;Diamond et al 1986;Sharma & Mittra 1988;Mahapatra et al 1991). Although recycling of RS offers agronomic benefits that are essential for sustainable rice farming, it also presents practical problems.…”
Section: Introductionmentioning
confidence: 99%
“…Literature also support of S. bispinosa is an excellent organic amendment for sub-tropical agro climatic conditions. 17,18 Sharma & Mitra 19 found enhanced productivity of main and succeeding crops due to application of Sesbania aculeata as green manure. The possible reasons for highest yield with Sesbania may be due to its easy and rapid decomposition, highest dry matter supplied and early release of nutrients to the crop.…”
Section: Resultsmentioning
confidence: 99%